2013
DOI: 10.1037/a0033542
|View full text |Cite
|
Sign up to set email alerts
|

Great expectations: Different high-risk activities satisfy different motives.

Abstract: Research on people's motives for engaging in high-risk activities has typically been viewed through the single-focused lens of sensation seeking. We provide evidence that comprehensively challenges that view. First, we develop and confirm the structure of a 3-factor measure of motives: the Sensation Seeking, Emotion Regulation, and Agency Scale (SEAS; Study 1). We then use the SEAS to provide evidence of differential motives for 2 high-risk activities: skydiving and mountaineering. The motive for skydiving is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 80 publications
4
113
1
5
Order By: Relevance
“…Each inventory contains 18 items with a seven-point Likert scale response mode ranging from one (completely disagree) to seven (completely agree). Barlow et al (2013) found evidence to support a three-factor structure for the Between and While inventories; however, they found that a two-factor model was a better fit to the data for the After inventory, with Agency and Emotion Regulation being combined into a single factor (i.e., agentic emotion regulation). Cronbach's alpha (α) displayed good internal consistency for each factor: Between participation inventory (α ≥ 0.84), While participating inventory (α ≥ 0.70), and After participation inventory (α ≥ 0.89).…”
Section: Scalesmentioning
confidence: 97%
See 4 more Smart Citations
“…Each inventory contains 18 items with a seven-point Likert scale response mode ranging from one (completely disagree) to seven (completely agree). Barlow et al (2013) found evidence to support a three-factor structure for the Between and While inventories; however, they found that a two-factor model was a better fit to the data for the After inventory, with Agency and Emotion Regulation being combined into a single factor (i.e., agentic emotion regulation). Cronbach's alpha (α) displayed good internal consistency for each factor: Between participation inventory (α ≥ 0.84), While participating inventory (α ≥ 0.70), and After participation inventory (α ≥ 0.89).…”
Section: Scalesmentioning
confidence: 97%
“…Given that Barlow et al (2013) found a two-factor structure to be most appropriate for the SEAS After inventory, we analyzed our data with two-and threefactor models in order to see if the translated version confirmed these initial findings. In addition to the criteria mentioned above, we used the Deviance Information Criteria (DIC) to compare the two-and three-factor G-SEAS After inventory as recommended by Asparouhov, Muthén, and Morin (2015).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 3 more Smart Citations